Genomic patterns in Acropora cervicornis show extensive population structure and variable genetic diversity. Issue 16 (30th June 2017) - Drury, Crawford; Schopmeyer, Stephanie; Goergen, Elizabeth; Bartels, Erich; Nedimyer, Ken; Johnson, Meaghan; Maxwell, Kerry; Galvan, Victor; Manfrino, Carrie; Lirman, Diego
Abstract: Threatened Caribbean coral communities can benefit from high‐resolution genetic data used to inform management and conservation action. We use Genotyping by Sequencing (GBS) to investigate genetic patterns in the threatened coral, Acropora cervicornis, across the Florida Reef Tract (FRT) and the western Caribbean. Results show extensive population structure at regional scales and resolve previously unknown structure within the FRT. Different regions also exhibit up to threefold differences in genetic diversity (He), suggesting targeted management based on the goals and resources of each population is needed. Patterns of genetic diversity have a strong spatial component, and our results show Broward and the Lower Keys are among the most diverse populations in Florida. The genetic diversity of Caribbean staghorn coral is concentrated within populations and within individual reefs (AMOVA), highlighting the complex mosaic of population structure. This variance structure is similar over regional and local scales, which suggests that in situ nurseries are adequately capturing natural patterns of diversity, representing a resource that can replicate the average diversity of wild assemblages, serving to increase intraspecific diversity and potentially leading to improved biodiversity and ecosystem function. Results presented here can be translated into specific goals for the recovery of A. cervicornis, including active focus on low diversity areas, protection of high diversity and connectivity, and practical thresholds for responsible restoration. Abstract : Extensive population structure in Caribbean Acropora cervicornis is complemented by previously unresolved structure within the Florida Reef Tract. In this area, genetic diversity varies widely, with a strong spatial component that may be important for management and conservation decisions.